Sub sea surface temperatures in the Polar North Atlantic during the Holocene: Planktic foraminiferal Mg/Ca temperature reconstructions. (January 2014) - Aagaard-Sørensen, Steffen; Husum, Katrine; Hald, Morten; Marchitto, Thomas; Godtliebsen, Fred
Holocene sea surface temperatures in the eastern Fram Strait are reconstructed based on Mg/Ca ratios measured on the planktic foraminifer Neogloboquadrina pachyderma (sin). The reconstructed sub sea surface temperatures (sSSTMg/Ca ) fluctuate markedly during the earliest Holocene at 11.7 and 10.5 kyr BP. This is probably in response to the varying presence of sea-ice and deglacial meltwater. Between 10.5–7.9 kyr BP, the sSSTMg/Ca values are relatively high ( 4°C) and more stable reflecting high insolation and intensified poleward advection of Atlantic Water. After 7.9 kyr BP, the sSSTMg/Ca values decline to an average of 3°C throughout the mid-Holocene. These changes can be attributed to a combined effect of reduced poleward oceanic heat advection and a decline in insolation as well as a gradually increased influence of eastward migrating Arctic Water. The sSSTMg/Ca values increase and vary between 2.1°C and 5.8°C from 2.7 kyr BP to the present. This warming is in contrast to declining late-Holocene insolation and may instead be explained by factors including increased advection of oceanic heat to the Arctic region possibly insulated beneath a widening freshwater layer in the northern North Atlantic in conjunction with a shift in calcification season and/or depth habitat of N. pachyderma (sin).